Peran Collaborative Governance Dalam Meningkatkan Efektivitas Penanggulangan Kemiskinan Kota Probolinggo - Mastina Maksin; Verto Septiandika; Eko Yudianto Yunus; Renny Candradewi Puspitarini; Nurul Faizzah (Universitas Mbojo Bima, 2025)
This study aims to analyze the role of collaborative governance in enhancing the effectiveness of poverty alleviation policies in Probolinggo City. Poverty is a multidimensional issue that cannot be addressed by the government alone, thus requiring the involvement of non-state actors such as NGOs, the private sector, and the community. Collaborative governance is chosen as the approach because it emphasizes participation, transparency, and accountability in the policy-making process. This research uses a qualitative method with data collected through interviews, observation, and documentation. The findings show that cross-sector collaboration improves policy effectiveness, both in terms of administrative output and substantive outcomes experienced directly by the community. However, challenges such as weak coordination and resistance from parts of the community remain. Therefore, strengthening sustainable collaborative mechanisms is necessary to ensure the long-term success of poverty alleviation policies.